caricato da Utente18731

# elettrotecnica formulario

annuncio pubblicitario
```X se // con C.C. X se – con C.A.
Esercizio 1. t&lt;0 e t-&gt;infin.
L
|C
t&gt;0. (C) LKT) Vc+Vth=Eo
LKC) ic=ith |
ic=C Vc&deg;
-&gt;Vc+Rth ith=0 -&gt;Vc+Rth ic=0
-&gt;Vc+Rth C Vc&deg;=0 -&gt;Vc&deg;+ Vc/Rth C=0
t&gt;0. (L) LKT) VL+Vth=Eo
LKC) iL=ith |
VL=L iL&deg;
-&gt;VL+Rth ith=0 -&gt;VL+Rth iL=0
-&gt;L iL&deg;+Rth iL=0 -&gt;iL&deg;+ iL Rth /L=0
(C)π=Rth C s| (L)π = L/Rth s|π=-1/ π π  −1
K=k(0+)- k(inf).
Esercizio 3. Fasori. ZL=jππΏ
Zc=-j (1/ππΆ) | ZR=R |Gener:
r cos(ππ‘)=r | r sin(ππ‘)=-r
r cos(ππ‘ + πΌ)= r (cos πΌ+jsin πΌ)
r sin(ππ‘ + πΌ)= r (cos πΌ-π/2+jsin πΌ-π/2)
S=1/2 (VI*)=1/2 (I I* Z)
Esercizio2. Esempio con iL.
(Delta&gt;0) iL eq=A π π1π‘ +Bπ π2π‘ +iL(inf)
I. iL eq (t=0)= iL (0+)
II. iL eq&deg; (t=0) = iL &deg; (0+)
(Delta=0) iL eq=A π π1π‘ +Bπ‘π π2π‘
I. A= iL (0+)
II. πA+B= iL&deg; (0+)
(Delta&lt;0) iL eq=π πΌπ‘ (Acosπ½+Bsinπ½)
I. A=iL(0+)+iL(inf)
II. [iL&deg;(0+)+πΌ (iL(0+)-iL(inf))]/π½
|
X se // con C.C. X se – con C.A.
Esercizio 1. t&lt;0 e t-&gt;infin.
L
|C
t&gt;0. (C) LKT) Vc+Vth=Eo
LKC) ic=ith |
ic=C Vc&deg;
-&gt;Vc+Rth ith=0 -&gt;Vc+Rth ic=0
-&gt;Vc+Rth C Vc&deg;=0 -&gt;Vc&deg;+ Vc/Rth C=0
t&gt;0. (L) LKT) VL+Vth=Eo
LKC) iL=ith |
VL=L iL&deg;
-&gt;VL+Rth ith=0 -&gt;VL+Rth iL=0
-&gt;L iL&deg;+Rth iL=0 -&gt;iL&deg;+ iL Rth /L=0
(C)π=Rth C s| (L)π = L/Rth s|π=-1/ π π  −1
K=k(0+)- k(inf).
Esercizio 3. Fasori. ZL=jππΏ
Zc=-j (1/ππΆ) | ZR=R |Gener:
r cos(ππ‘)=r | r sin(ππ‘)=-r
r cos(ππ‘ + πΌ)= r (cos πΌ+jsin πΌ)
r sin(ππ‘ + πΌ)= r (cos πΌ-π/2+jsin πΌ-π/2)
S=1/2 (VI*)=1/2 (I I* Z)
Esercizio2. Esempio con iL.
(Delta&gt;0) iL eq=A π π1π‘ +Bπ π2π‘ +iL(inf)
I. iL eq (t=0)= iL (0+)
II. iL eq&deg; (t=0) = iL &deg; (0+)
(Delta=0) iL eq=A π π1π‘ +Bπ‘π π2π‘
I. A= iL (0+)
II. πA+B= iL&deg; (0+)
(Delta&lt;0) iL eq=π πΌπ‘ (Acosπ½+Bsinπ½)
I. A=iL(0+)+iL(inf)
II. [iL&deg;(0+)+πΌ (iL(0+)-iL(inf))]/π½
|
X se // con C.C. X se – con C.A.
Esercizio 1. t&lt;0 e t-&gt;infin.
L
|C
t&gt;0. (C) LKT) Vc+Vth=Eo
LKC) ic=ith |
ic=C Vc&deg;
-&gt;Vc+Rth ith=0 -&gt;Vc+Rth ic=0
-&gt;Vc+Rth C Vc&deg;=0 -&gt;Vc&deg;+ Vc/Rth C=0
t&gt;0. (L) LKT) VL+Vth=Eo
LKC) iL=ith |
VL=L iL&deg;
-&gt;VL+Rth ith=0 -&gt;VL+Rth iL=0
-&gt;L iL&deg;+Rth iL=0 -&gt;iL&deg;+ iL Rth /L=0
(C)π=Rth C s| (L)π = L/Rth s|π=-1/ π π  −1
K=k(0+)- k(inf).
Esercizio 3. Fasori. ZL=jππΏ
Zc=-j (1/ππΆ) | ZR=R |Gener:
r cos(ππ‘)=r | r sin(ππ‘)=-r
r cos(ππ‘ + πΌ)= r (cos πΌ+jsin πΌ)
r sin(ππ‘ + πΌ)= r (cos πΌ-π/2+jsin πΌ-π/2)
S=1/2 (VI*)=1/2 (I I* Z)
Esercizio2. Esempio con iL.
(Delta&gt;0) iL eq=A π π1π‘ +Bπ π2π‘ +iL(inf)
I. iL eq (t=0)= iL (0+)
II. iL eq&deg; (t=0) = iL &deg; (0+)
(Delta=0) iL eq=A π π1π‘ +Bπ‘π π2π‘
I. A= iL (0+)
II. πA+B= iL&deg; (0+)
(Delta&lt;0) iL eq=π πΌπ‘ (Acosπ½+Bsinπ½)
I. A=iL(0+)+iL(inf)
II. [iL&deg;(0+)+πΌ (iL(0+)-iL(inf))]/π½
X se // con C.C. X se – con C.A.
Esercizio 1. t&lt;0 e t-&gt;infin.
L
|C
t&gt;0. (C) LKT) Vc+Vth=Eo
LKC) ic=ith |
ic=C Vc&deg;
-&gt;Vc+Rth ith=0 -&gt;Vc+Rth ic=0
-&gt;Vc+Rth C Vc&deg;=0 -&gt;Vc&deg;+ Vc/Rth C=0
t&gt;0. (L) LKT) VL+Vth=Eo
LKC) iL=ith |
VL=L iL&deg;
-&gt;VL+Rth ith=0 -&gt;VL+Rth iL=0
-&gt;L iL&deg;+Rth iL=0 -&gt;iL&deg;+ iL Rth /L=0
(C)π=Rth C s| (L)π = L/Rth s|π=-1/ π π  −1
K=k(0+)- k(inf).
Esercizio 3. Fasori. ZL=jππΏ
Zc=-j (1/ππΆ) | ZR=R |Gener:
r cos(ππ‘)=r | r sin(ππ‘)=-r
r cos(ππ‘ + πΌ)= r (cos πΌ+jsin πΌ)
r sin(ππ‘ + πΌ)= r (cos πΌ-π/2+jsin πΌ-π/2)
S=1/2 (VI*)=1/2 (I I* Z)
Esercizio2. Esempio con iL.
(Delta&gt;0) iL eq=A π π1π‘ +Bπ π2π‘ +iL(inf)
I. iL eq (t=0)= iL (0+)
II. iL eq&deg; (t=0) = iL &deg; (0+)
(Delta=0) iL eq=A π π1π‘ +Bπ‘π π2π‘
I. A= iL (0+)
II. πA+B= iL&deg; (0+)
(Delta&lt;0) iL eq=π πΌπ‘ (Acosπ½+Bsinπ½)
I. A=iL(0+)+iL(inf)
II. [iL&deg;(0+)+πΌ (iL(0+)-iL(inf))]/π½
|
```